2010
DOI: 10.1016/j.postharvbio.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evaluation of new antagonists for their efficacy against postharvest brown rot of peaches

Abstract: Technology , 55, 174-181. DOI: 10.1016, 55, 174-181. DOI: 10. /j.postharvbio.2009. 9 10 You may download, copy and otherwise use the AAM for non-commercial purposes provided that your 11 license is limited by the following restrictions: 12 13 (1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND 14 license. 15(2) The integrity of the work and identification of the author, copyright owner, and publisher must be 16 preserved in any copy. (Janisiewicz and Korsten, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 55 publications
(2 reference statements)
0
56
0
Order By: Relevance
“…For example, Zhang et al [20] tested 210 isolates on peaches. However this approach is labour-intensive and hence may restrict the number of microbes that can be screened.…”
Section: In Vitro and In Vivo Screening Of Microbes Against M Laxamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zhang et al [20] tested 210 isolates on peaches. However this approach is labour-intensive and hence may restrict the number of microbes that can be screened.…”
Section: In Vitro and In Vivo Screening Of Microbes Against M Laxamentioning
confidence: 99%
“…For example, nutrients leaked from artificial wounds on fruit surfaces may have affected the mechanism of inhibition used by the BCAs. This high level of attrition of potential candidates between in vitro and in vivo screens is common [20]. and average of lesion diameter (mm) on plum (c).…”
Section: In Vitro and In Vivo Screening Of Microbes Against M Laxamentioning
confidence: 99%
See 1 more Smart Citation
“…No preparation was required for the clear apple juice. Patulin was eluted with water:acetonitril:perchloric acid (95:5:0.095) and separated on a 5-μm C 18 chromatographic column (150 mm x 4.6 mm) at a fl ow rate of 1.0 mL min -1 . The UV detector wavelength was set at 276 nm and sample injection volume at 50 μL.…”
Section: Culture Preparationmentioning
confidence: 99%
“…Some authors have shown that the best antagonist against fungi that cause fruit decay is the very microfl ora from their surfaces (17)(18)(19). Our results confirm that microfl ora naturally occurring on fruit surfaces could provide effective protection against fungal growth and patulin accumulation.…”
Section: Apple Juicementioning
confidence: 99%